Simplified proposal for assessment of quality management on class entities (Revista Brasileira de Contabilidade e Gestão, 2014)
This article aims to propose a simplified model for assessing the mana that enables to measure and classify the different levels of manage ement of associations ent in order to help organizations improve their organizational performance. It was performed a literature search on the historical evolution of quality management using the eight criteria of the Excellence Model Management (MEG) of the National Quality Foundation (FNQ) - Leadership, Strategies and Plans, Customers, Society, Information and Knowledge, People, Processes and Outcomes. From the description of the quality and management for excellence presented a Proposed Simplified Evaluation of Quality Management in Class Entities, which aims to assist leaders in a systemicn vision necessary to manage this type of organization, as this is a instrume subsidies for decision making and provide input into a plan for organizational management.
Keywords: quality management; excellence model; entities class; proposed simplified evaluation of quality managemnent; quality